About derivations on G-algebras - Wahiba Messirdi; Ahlam Fallatah (Journal of Taibah University for Science, 2020)
This paper presents several results from the study of certain properties of G-algebras. More precisely, we will show that, if N is a normal subset of a finite G-algebra X, then the order of N divides the order of X. In addition, we will give an important result about the set of derivations on a finite G-algebra X, and give a condition on this set to determine the commutativity and the associativity of X.